Evaluation of the postoperative course of East Asian eyelid reconstruction with free tarsoconjunctival graft transplantation: A Japanese single-centre retrospective study. (September 2022) - Ominato, Jun; Oyama, Tokuhide; Cho, Hiroyuki; Shiozaki, Naoya; Eguchi, Koichi; Fukuchi, Takeo
Summary: Although eyelid reconstruction by transplanting an autologous free tarsoconjunctival graft (FTG) is a well-established technique, few studies have examined the postoperative course of FTG transplantation for East Asian eyelids, including those of Japanese patients. Therefore, this study investigated complication and reoperation rates after FTG transplantation in the reconstruction of East Asian (Japanese) eyelids. This study included 42 eyelids wherein posterior lobe reconstruction after resection of a malignant tumour of the eyelid was performed by FTG transplantation between 2007 and 2019 at Niigata University Medical and Dental Hospital. We investigated complications and need for revision surgery during the patients' postoperative courses. The relationship between postoperative complications, tumour diameter, and eyelid defect width was statistically examined. Of 42 cases reconstructed with FTG, the upper eyelid was reconstructed in 23. Postoperative complications were observed in 12 cases (52%): entropion in eight and corneal epithelial disorder in four. Revision surgery was required in three of those cases (13%). There were 19 cases of lower eyelid reconstruction. Postoperative complications were observed in seven cases (32%): ectropion in three and corneal epithelial disorder in two and one lower eyelid ptosis. Two of these cases (11%) required revision surgery. There was no statistically significant difference in tumour diameter between cases with and without postoperative complications. There was also no significant association between the width of the eyelid defect and the presence/absence of complications. Entropion and ectropion were more likely to occur in the upper and lower eyelids, respectively. For Japanese eyelids, complication rates after FTG transplantation were approximately 50% and 30% for the upper and lower eyelids, respectively. The revision surgery rate was approximately 10% for both upper and lower eyelids. As these revision surgery rates are low, FTG transplantation may be an option for the reconstruction of Japanese eyelids.